2003
DOI: 10.1183/09031936.03.00075702
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor activation and mitogenic synergism in airway smooth muscle cells

Abstract: Simultaneous treatment of human airway smooth muscle (HASM) cells with lysophosphatidic acid (LPA) and epidermal growth factor (EGF) leads to strikingly synergistic stimulation of mitogenesis. The purpose of this study was to explore potential sites for signal integration mediating synergism, focusing on extracellular signal-regulated kinase (ERK) and transcription factors involved in proliferation and inflammation as likely candidates.Activation of ERK was analysed by immunoblotting. Transcription factor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Lysophosphatidic acid-dependent enhancement of EGF-induced proliferation of human airway SMC also does not correlate with ERK 1/2 activation. However, in this case, the low molecular weight G protein, Rho, appears to mediate the synergistic response, whereas p70 S6 kinase does not [49]. The effectors of p70 S6 kinase and Rho that mediate these synergistic proliferative responses have not been identified.…”
Section: Discussionmentioning
confidence: 97%
“…Lysophosphatidic acid-dependent enhancement of EGF-induced proliferation of human airway SMC also does not correlate with ERK 1/2 activation. However, in this case, the low molecular weight G protein, Rho, appears to mediate the synergistic response, whereas p70 S6 kinase does not [49]. The effectors of p70 S6 kinase and Rho that mediate these synergistic proliferative responses have not been identified.…”
Section: Discussionmentioning
confidence: 97%
“…LPA is a potent bioactive lipid that mediates several cellular responses such as proliferation, differentiation, suppression of apoptosis, tumor metastasis, and cytoskeletal reorganization (15,(21)(22)(23)(24)(25)(26)(27)(28). LPA mediates the broad range of cellular responses through the G-protein-coupled receptors LPA 1 /Edg-2, LPA 2 /Edg-4, and LPA 3 /Edg-7 (19).…”
Section: Discussionmentioning
confidence: 99%
“…In guinea pigs, administration of exogenous LPA into the airway enhances the response to acetylcholine (22) and infiltration of neutrophils (23). Other reports have shown that LPA induces airway smooth muscle contractility (24), proliferation (25), and transcription factor activation (26). In ovarian cancer cells, LPA induces both IL-6 and IL-8 expression (27,28).…”
mentioning
confidence: 98%
“…However, there is also some suggestion that "normal" stimuli such as bronchoconstrictor agonists (114,233,341) and other locally produced factors (5,53,75) could trigger increased proliferation under certain conditions, leading to the asthmatic phenotype. In this regard, interactions between GPCRs and RTKs may be important (18,67,68,155,162,303). For example, M 2 muscarinic receptors can potentiate TGF-␤-induced enhancement of proliferation (216).…”
Section: Asm In Airway Remodelingmentioning
confidence: 99%